STUDI GAYA KEPEMIMPINAN DAN DINAMIKA KELOMPOK PADA POKDAKAN DI DESA PONORAGAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - jumadri, eza sanjaya; Darmansyah, Oon; Erwiantono (Fakultas Perikanan Universitas Pekalongan, 2025)
This research aims to determine the group characteristics, members' perceptions of leadership styles, and the level of group dynamics among fish farmers in Ponoragan Village, Loa Kulu District, Kutai Kartanegara Regency.The research was conducted from September 2024 to April 2025 in Ponoragan Village, Loa Kulu District, Kutai Kartanegara Regency.The sampling method used in this study is the Census method with a sample size of 38 fish farmers from three groups of fish farmers, namely: Kelompok Cahaya Ulam, Mina Kolam Mandiri Jaya, and Sumber Sari Makmur.The types of data used in this research are primary and secondary data.Data analysis uses tabular-based descriptive analysis, which is then presented in the form of tables.Data collection through questionnaires and interviews was then analyzed using descriptive statistics.The research results show that the characteristics of the group leaders and members fall within the age range of 25-60 years, with the majority having a high school education.The number of dependents ranges from 3-5 people, with an income range of Rp. 2,000,000-Rp. 4,000,000.The dominant leadership style is authoritarian in the Cahaya Ulam group, while other leadership styles are democratic in the Mina Kolam Mandiri Jaya group, and relaxed in the Sumber Sari Makmur group.Even the level of group dynamics varies among the groups.This research is expected to provide information and input to the public regarding more effective leadership styles and group dynamics of fish farmer groups. Keywords: Characteristics, Leadership Style, Group Dynamics